KARAKTERISASI BIJIH MANGAN DI KABUPATEN TIMOR TENGAH UTARA - Elisabeth Korbafo; Maria Magdalena Kolo (Saintek Lahan Kering, 2021)
The potential for manganese reserves in Indonesia is nquite high nin all islands, including in NTT, especially in North Central Timor Regency. Goverment regbulation No.7 of 2012 concerning the prohibition of selling raw mining materials abroad implies that we must process them into intermediate goods or final products so that these mining materials have a high selling value. The purpose of this study was determine the content of manganese contained in manganese ores scattered in North Centr Timor Regency.